(untitled) (Biological Sciences - PJSIR, 2005)
Button mushrooms (Agaricus bisporus) were incorporated into six table delicacies and six traditional Pakistani dishes. Protein content of the mushroom-fortified dishes increased from 8.44% to 67.50%. Organoleptic evaluations showed that all the mushroom-fortified table delicacies and traditional dishes showed significant improvement in their acceptability.